Analisis Elemen Laporan Keuangan dalam Kerangka Konseptual Akuntansi - Helena Febriyanti Tambunan; Salsabila Aulia Putri; Vanesa Putri Firdianti Sagita; Lusiana Fitriani; Yulius Tjandra (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
This study aims to analyze the elements of financial statements within the conceptual framework of accounting, including assets, liabilities, equity, revenue, and expenses, as well as the recognition and measurement of these elements. This study is motivated by the importance of high-quality, relevant, and reliable financial reporting in supporting economic decision-making amid increasingly intense business competition. This study employs a qualitative method using a literature review approach by examining various scientific sources, such as journals, books, and accounting standards related to the conceptual framework of accounting. The findings indicate that the conceptual framework of accounting serves as a crucial theoretical foundation for the preparation of financial statements and assists accountants in addressing accounting issues not explicitly addressed in accounting standards. Furthermore, the elements of financial statements play a vital role in generating relevant and reliable financial information for users of financial statements. Proper recognition and measurement of these elements also contribute to enhancing the quality and credibility of financial reporting. This study is expected to deepen understanding of the importance of the conceptual framework of accounting in producing high-quality financial statements that can support effective economic decision-making.